Preparation of Patchouli Oil Microemulsion Gel and Its Topical Application to Ameliorate Atopic Dermatitis in Mice - Tingting Chen; Changjin Xu; Min Wang; Yan Cui; Riqing Cheng; Wenyao Zhang; Xin Gao; Laibing Wang; Herima Qi; Shuyan Yu; Jianping Chen; Lan Ma; et al. (Gels, 2024)
Patchouli oil (PO) is a natural substance famous for its immune-enhancing and anti-inflammatory effects. Atopic dermatitis (AD) is characterized by epidermal gene mutations, skin barrier dysfunction, and immune dysregulation, making patchouli volatile oil a potential candidate for AD treatment. Initially, PO was mixed with ethyl oleate (EO), castor oil ethoxylated ether-40 (EL-40), anhydrous ethanol, and water to form a patchouli oil microemulsion (PO-ME) system. The formulation ratios were optimized using the Box–Behnken design-effect surface method, and their products were characterized for type, particle size, polydispersity index (PDI), and appearance. Additionally, patchouli oil microemulsion gel (PO-MEG) was developed with a specified concentration of 1.5% carbomer-940 as the matrix, and its pH, stability, viscosity, and permeability were evaluated. We assessed the irritation tests of PO-MEG using a rat self-control model and the Cell Counting Kit-8 (CCK-8) assay. The results demonstrated that should be attributed to non-irritating. This study also assessed the efficacy of optimized PO-MEG on AD-like symptoms using a 2,4-dinitrochlorobenzene (DNCB)-induced BALB/c mouse model. Compared with the model group, the in vivo efficacy studies have shown the PO-MEG group significantly reduces dermatitis scores, mast cell counts, epidermal thickness, and levels of pro-inflammatory cytokines and immune factors in skin homogenates. This suggests that PO-MEG would become a safer topical formulation for treating atopic dermatitis.